2017
DOI: 10.1016/j.sdentj.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of fluoride concentration in drinking water and common beverages in United Arab Emirates (UAE)

Abstract: The tap water, bottled water and beverages available in U.A.E show varying concentrations of fluoride, however none showed the optimal level necessary to prevent dental caries. Dental professionals in U.A.E should be aware of the fluoride concentrations before prescribing fluoride supplements to children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 17 publications
1
14
3
Order By: Relevance
“…The comparison of the fluoride concentration in the glass-bottled soft drinks of this study with the literature values is given in Table 4. The fluoride concentrations of Coca Cola reported in United Arab Emirates [30], China [29], Brazil [37], Mexico [10], UK [38], Sri Lanka [39] and India [40] are 0.08, 0.243, 0.092, 0.34, 0.26, 0.122 and 0.32 mg/L, respectively, are higher than the fluoride concentration of glass-bottled Coca Cola of the present study.…”
Section: Comparison Of Fluoride Levels In the Soft Drinks Marketed Incontrasting
confidence: 72%
See 3 more Smart Citations
“…The comparison of the fluoride concentration in the glass-bottled soft drinks of this study with the literature values is given in Table 4. The fluoride concentrations of Coca Cola reported in United Arab Emirates [30], China [29], Brazil [37], Mexico [10], UK [38], Sri Lanka [39] and India [40] are 0.08, 0.243, 0.092, 0.34, 0.26, 0.122 and 0.32 mg/L, respectively, are higher than the fluoride concentration of glass-bottled Coca Cola of the present study.…”
Section: Comparison Of Fluoride Levels In the Soft Drinks Marketed Incontrasting
confidence: 72%
“…The fluoride concentrations of Pepsi reported in United Arab Emirates [30], China [29], India [6], Sri Lanka [39] and India [40] are 0.09, 0.126, 0.22, 0.142, 0.21 mg/L, respectively and are lower than 0.23 mg/L fluoride concentration in the glass-bottled Pepsi of the present study. The fluoride concentration of Mirinda reported in India [6,40] is higher than that of the glass-bottled Mirinda of present study and the fluoride concentration of Mirinda reported in United Arab Emirates [30] and Sri Lanka [39] is lower than that of the present study.…”
Section: Comparison Of Fluoride Levels In the Soft Drinks Marketed Incontrasting
confidence: 63%
See 2 more Smart Citations
“…Higher fluoride content of up to 4.14 mg F/L (MOHAMED, 2016) and 4.8 mg/L (AHIROPOULOS, 2006) have been reported in bottled water. In other studies, also lower fluoride levels in bottled water have been determined: 0.04 -0.3 mg F/L (TARUN et al, 2017) and 0.1 -0.8 mg F/L (TOUMBA et al, 1994). The value of 2.25 mg F/L of Swan water is higher than 0.14 -0.41 mg F/L reported for spring water in Kerang province, Plateau State ((DIBAL and LAR, 2005).…”
Section: Resultsmentioning
confidence: 71%